The LOCATA challenge data corpus for acoustic source localization and tracking - Löllmann,HW; Evers,C; Schmidt,A; Mellmann,H; Barfuss,H; Naylor,PA; Kellermann,W (IEEE, 2018)
Algorithms for acoustic source localization andtracking are essential for a wide range of applications suchas personal assistants, smart homes, tele-conferencing systems,hearing aids, or autonomous systems. Numerous algorithms havebeen proposed for this purpose which, however, are not evaluatedand compared against each other by using a common database sofar. The IEEE-AASP Challenge on sound source localization andtracking (LOCATA) provides a novel, comprehensive data corpusfor the objective benchmarking of state-of-the-art algorithmson sound source localization and tracking. The data corpuscomprises six tasks ranging from the localization of a singlestatic sound source with a static microphone array to the trackingof multiple moving speakers with a moving microphone array.It contains real-world multichannel audio recordings, obtainedby hearing aids, microphones integrated in a robot head, aplanar and a spherical microphone array in an enclosed acousticenvironment as well as positional information about the involvedarrays and sound sources represented by moving human talkersor static loudspeakers.